Desempenho bioeconômico de clones de palma forrageira sob diferentes manejos hídricos - HENRIQUES, Leandro Calixto (2016)
Studies have been conducted in order to demonstrate the benefits of the use of irrigation in the annual yield of forage cactus. But they still need improvement, as soon as they do not address the need for water culture, and the less different clones. The purpose of this proposal was to evaluate the adoption of different water management in the plantation system of forage cactus clones in semi-arid environment. The experiment was conducted in the city of Serra Talhada-PE (2012/2014), with cactus pear clones Orelha de Elefante Mexicana - OEM (Opuntia stricta), IPA Sertânia - IPA e Miúda - MIU (Nopalea cochenillífera), Submitted to three water schemes: rainfed (S), irrigation without coverage (ISC) and irrigation with mulch on the soil (ICC). The experiment was arranged in randomized block design in a split plot arrangement with three replications. At the time of harvest were recorded biometric data of the plant and cladodes. The crop yield was determined in fresh and dry base in tonnes per hectare. From these data were calculated water use efficiency indicators (EUA), economic productivity and economic viability of the adoption of different water management. For this, the total production costs for implementation and maintenance of the irrigation system were calculated, driving culture, gross and net profitability, and benefit / cost ratio. The experimental data were subjected to analysis of variance when necessary compared by Tukey test at 5% probability. There was no interaction among the factors water regimes and clones. On the other hand, the yield of green matter (MV) was no significant difference (p> 0.05) with the isolated effect of clones and water regimes, highlighting, in that order, the OEM and the ICC. In the dry matter (MS) there was difference only for water systems, where the ICC showed better performance in relation to other treatments. Water efficiency was higher for o OEM (EUA~15,48 kg MS ha-1 mm-1), followed by IPA (EUA~9,64 kg MS ha-1 mm-1) and MIU (EUA~7,83 kg MS ha-1 mm-1). In terms of economic analysis, the total cost of production of irrigated forage cactus was R$ 8.442,46 ha-1. Considering the fate of forages, OEM clone showed the average net income of R$ 4.745,49 and the benefit / cost ratio of 0,57, indicating no economic viability. Already considering the sale of cladodes as "seed" the Miúda showed higher values of net revenues and cost/benefit, averaging R$ 57.902,55 and 6,95 respectively, that is, for every R$ 1,00 investment in irrigated forage palm production system for an average return of R$ 6,95. Thus it is concluded that (i) the OEM clone with the irrigation events showed a good growth performance, particularly for the sale of fodder, and MIU for the sale of cladodes intended for "seed". (ii) the combination of irrigation with the use of mulch contributed to the production increase of forage cactus, but did not minimize the disparity in productivity Nopalea genre clones in relation to the genres Opuntia.